A method based on plateletpheresis to obtain functional platelet, CD3+ and CD14+ matched populations for research immunological studies. Issue 10 (16th July 2022) - Pablo‐Torres, Carmela; Delgado‐Dolset, María Isabel; Sanchez‐Solares, Javier; Mera‐Berriatua, Leticia; Núñez Martín Buitrago, Lucía; Reaño Martos, Mar; Bueno, José Luis; Escribese, Maria M.; Barber, Domingo; Gomez‐Casado, Cristina
Abstract: Background: In previous studies with peripheral blood cells, platelet factors were found to be associated with severe allergic phenotypes. A reliable method yielding highly concentrated and pure platelet samples is usually not available for immunological studies. Plateletpheresis is widely used in the clinics for donation purposes. In this study, we designed a protocol based on plateletpheresis to obtain Platelet‐Rich Plasma (PRP), Platelet‐Poor Plasma (PPP) as well as CD3 + and CD14 + cells matched samples from a waste plateletpheresis product for immunological studies. Methods: Twenty‐seven subjects were voluntarily subjected to plateletpheresis. PRP, PPP and blood cell concentrate contained in a leukocyte reduction system chamber (LRSC) were obtained in this process. CD3 + and CD14 + cells were isolated from the LRSC by density‐gradient centrifugation and positive magnetic bead isolation. RNA was isolated from PRP, CD3 + and CD14 + cell samples and used for transcriptomic studies by Affymetrix. PRP and PPP samples were used for platelet protein quantification by multiplex assays. Results: A reliable high yield method to obtain matched samples of PRP, PPP, CD3 + and CD14 + from a single donor for RNA and protein analyses has been designed. The RNA quality indicators (RQI) routinely used for other cell types were not suitable for platelet RNA characterization. Despite this, the platelet RNA was valid for transcriptomic studies by Affymetrix, as platelet transcripts obtained in our previous studies were confirmed in PRP samples. Platelet samples were enriched in platelet factors as determined in protein multiplex analysis. Conclusions: We have developed a method that yields not only high content and pure platelet samples from a single donor but also CD3 + and CD14 + matched samples that can be used for RNA and protein analyses in immunological studies. Abstract : We describe a platelet isolation method based on plateletpheresis that allows to obtain pure, highly concentrated and functional platelet samples from a single donor. Additionally, matched CD3 + and CD14 + populations can be obtained from a waste product of plateletpheresis procedure. All the samples are suitable for omics studies.